2002
DOI: 10.14310/horm.2002.1485
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of phalangeal quantitative ultrasound in identifying reduced bone mineral status and increased fracture risk in adolescents with Turner syndrome

Abstract: ObJEcTIVE. bone health is a major concern in patients with Turner syndrome (TS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…9 Moreover, they found no differences in the total vBMD Z-score or the trabecular vBMD Z-score at the distal radius. Using ultrasound methods, comparable results were obtained by Zuckerman-Levin et al and Vierucci et al 24,26 As in our study, they found reduced phalangeal Ad-SoS, and radial and tibial SoS in girls and women with TS. As with pQCT data, abnormal QUS results may imply structural abnormalities in cortical bone in TS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…9 Moreover, they found no differences in the total vBMD Z-score or the trabecular vBMD Z-score at the distal radius. Using ultrasound methods, comparable results were obtained by Zuckerman-Levin et al and Vierucci et al 24,26 As in our study, they found reduced phalangeal Ad-SoS, and radial and tibial SoS in girls and women with TS. As with pQCT data, abnormal QUS results may imply structural abnormalities in cortical bone in TS.…”
Section: Discussionsupporting
confidence: 92%
“…28,29 This percentage is not higher than in a healthy population, because fractures are also common in youth, with 1/3 of all children sustaining at least 1 fracture before the age of 17 years. 30,31 Our finding varies from a paper by Vierucci et al 26 They found a slightly increased risk of fracture in TS girls. In the study, 62.5% of their TS patients had an Ad-SoS Z-score of <−2 and only 1 TS patient with positive history of fracture had normal QUS values, whereas 67% of our TS girls with a previous history of fracture had an Ad-SoS Z-score of >−2.…”
Section: Discussioncontrasting
confidence: 87%
“…AD-SOS and BUA are thought to be more sensitive in detecting the bone mineral status and fracture risk in girls with TS than BMD alone22. AD-SOS is a measure of the speed at which the ultrasound of a particular amplitude passes through the bone and soft tissue and reflects the bone architecture and elasticity23.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to prevent osteoporosis and fractures should been considered in TS subjects, just during pediatric age ( 87 ). In the first instance, bone mineral status should been assessed in childhood to detect TS subjects at increased risk of bone impairment and in order to carry out preventive measures ( 25 ). In particular, it is preferable to use diagnostic methods that take into account for reduced bone size of these patients, such as pQCT or volumetric transformation of DXA data ( 88 ).…”
Section: Management Of Bone Fragility In Tsmentioning
confidence: 99%
“…Moreover, the use of non-invasive and radiation-free tools, such as phalangeal quantitative ultrasound (QUS), can be particularly useful for routinely assessing of BMD in children and adolescents with TS ( 25 ).…”
Section: Management Of Bone Fragility In Tsmentioning
confidence: 99%